Clinical characteristics and care times in a chest pain unit of the emergency department of an argentine center - Grande Ratti, María Florencia (2023)
Objectives. To report the frequency of precordial pain, describe clinical characteristics, and care times. Methods. Retrospective descriptive study that  included consultations in the Chest Pain  Unit in 2021 in the emergency department of a private hospital in Argentina. Results. There were 1469 admissions for chest pain, yielding a frequency of 1.09% (95%CI 1.04-1.15). They were 52% men, mean age 62 years (SD ±15); 48% had hypertension and 32% dyslipidemia. The median time to initial ECG was 4.3 min (ICR 2.5-7.5); and 26 min (ICR 14-46) to medical evaluation. A total of 206 (14%) were hospitalized with a median of 3 days, 76% were admitted to a closed unit, 9% required non-invasive ventilation/mechanical ventilaction and in-hospital mortality was 2.9%. Those hospitalized presented shorter delay time to medical attention (p<0.01), and greater performance of complementary studies (p<0.01), with no differences in time to ECG (p=0.22). Conclusions. Care times were within the stipulated standards, being an important indicator of quality. Nursing was crucial, taking care of the correct triage, ECG on admission, and guaranteeing care until medical evaluation.